Malaysian graduates employability in post COVID-19: a swot analysis / Wong Sing Yun and Chi Yi Beh - Wong, Sing Yun; Chi, Yi Beh (Faculty of Business and Management ; UiTM Press, 2024)
The widespread impact of the COVID-19 pandemic has disrupted numerous facets of life, including education, career paths, and employment opportunities, affecting individuals, communities, and economies worldwide. This study delves into the realm of employability among Malaysian graduates post the COVID-19 crisis. Malaysia, known for its distinct socio-economic landscape, offers a captivating backdrop to explore the diverse challenges and opportunities faced by graduates seeking stable and meaningful employment in the aftermath of the pandemic. Employing SWOT analysis, this research comprehensively investigates the employability experiences of recent Malaysian graduates by drawing insights from a focused selection of literature concerning graduates' employment and its interplay with the Covid-19 situation. The study's outcomes highlight the critical need for adaptive policies and educational initiatives tailored to equip graduates with the essential skills and adaptable mindset required to excel in an evolving post-pandemic job market. Above all, the study underscores the significance of understanding and addressing the unique nuances of the Malaysian context while offering insights that can potentially benefit other regions grappling with similar employability challenges triggered by the pandemic's aftermath.